Pengaruh Literasi Keuangan Dan Pengelolaan Keuangan terhadap Keberlanjutan Usaha - Nurfadhilah, Ilfi; Yuliani, Nur Laila; Muhdiyanto, Muhdiyanto; Shofiyani, Dianah; Hana, Marissa Tri; Nugraheni, Nur Aisah; Candra, Septian Dwi (Universitas Muhammadiyah Metro, 2024)
Business sustainability Refers to the ability of an organization or company to operate in the long term by paying attention to the strategy and implementation carried out. This research aims to find out the influence of financial literacy on business desires, and determine the influence of financial management on business desires. This research uses quantitative methods. The population of this research is the Balcondes managers in 20 Balcondes in Borobudur. The sample in this study was 70 respondents using a purposive sampling method. The analytical tool used is SPSS 25. The results of this research show that financial literacy has no effect on business termination, and financial management has an effect on business termination